ظلال الاستفهام في قصص نورة فرج - الفياض، حنان أحمد عبدالله (جامعة مولود معمري تيزي وزو - كلية الآداب واللغات - مخبر تحليل الخطاب, 2020)
يأتي هذا البحث للكشف عن المعاني البلاغية العديدة والمتنوعة التي يخرج إليها الاستفهام عن أصل معناه، وهو طلب الفهم، وذلك من خلال التطبيق على مجموعتين قصصيتين للأديبة القطرية نورة فرج التي شكل الاستفهام ظاهرة أسلوبية واضحة في لغتها الأدبية أسهمت في تحقيق الإدهاش الذي يعد ضالة الأدباء. وركز البحث على العناصر التي جاء الاستفهام خادما لها، وهي: الشخصيات، والمتلقي، والشكل الفني. وقد ظهر من خلال هذا البحث أن تنوع السياقات بمعونة القرائن المحيطة يتبعه تنوع المعاني المستفادة من الاستفهام، وتعددها بشكل يعز على الحصر. وليست تلك المعاني لازمة لأداة من أدوات الاستفهام، ولذا نرى معاني مختلفة عن تلك التي تقررت في كتب النحو والبلاغة لدى الأقدمين. ومن تلك المعاني التي توصل إليها هذا البحث: الشك، والتحسر والتوجع، والاستكثار، والابتزاز، والتحير، والاستفزاز، والتحبب، إضافة إلى المعاني المقررة الأخرى كالتعجب والتقرير والإنكار. وقد تبين بالدراسة كيف استطاع الاستفهام أن يلقي بظلاله على شخصيات القصة، ويمكن من سبر أغوارها، كما أنه جاء ضامنا لتفاعل المتلقي وجعله شريكا في صناعة الحدث. كما أظهر البحث أيضاً أن الاستفهام قد اضفى وهجه على عتبات القصة وختاماتها بالصورة التي تمنحها دخولا فنيا مثيرا للمتابعة. وهكذا استطاعت الكاتبة أن توظف الاستفهام وسيلة فاعلة لصناعة قصصية تعتمد الإثارة والتشويق.
This research detects the multiple rhetorical meanings of the question, which differ from "seeking understanding" the standard meaning of the question. This research takes The Qatari novelist Norah Faraj's two collections of stories; who used the functions of Question as an effective way to create excitement and thrill in her stories. The research concentrates on the main element in which the question functions have been used, such as the characters, the receiver, and the style. And through the research, we recognized that the variety of situations in addition to the links surrounding these situations, is followed by variety in meanings understood from the question, and that causes multiple meanings which can be countless. That is not related to the question word itself; so we find different meanings that are not in grammar or rhetoric old books. From these meanings, which this research has clarified: doubt, sigh, aching, propagation, blackmail, hesitation, provocation and endearment, in addition to wonder, determination and denial. And by research, it was clear that the question has been the main theme of Faraj's works, as she used the question to make characters more deep and unique, and The question has linked the receiver to the story and made him a partner in the action, through referral, excitement, and thrill. The research also makes clear the effect of question on the style which made links between the thresholds and the endings, in which it has given the story coherence and has attracted the receiver to follow the events with so much thrill. Norah Faraj proved that she is skillful to use the question functions.
Keywords: المعانى البلاغية -- أدوات الاستفهام -- اللغة العربية